The effect of increased fruit and vegetable consumption on selected macronutrient and micronutrient intakes in four randomised-controlled trials. Issue 9 (24th May 2017) - Fulton, Sharon L.; McKinley, Michelle C.; Neville, Charlotte E.; Baldrick, Francina R.; Mulligan, Ciara; McCall, Damian O.; McCance, David R.; Edgar, J. D.; Elborn, J. S.; Young, Ian S.; Patterson, Chris C.; Woodside, Jayne V.
Abstract: Fruit and vegetable (FV) intake is associated with reduced risk of a number of non-communicable diseases. Research tends to focus on antioxidants, flavonoids and polyphenols contained in FV as the main beneficial components to health; however, increasing FV may also alter overall diet profile. Extra FV may be substituted for foods thought to be less healthy, therefore altering the overall macronutrient and/or micronutrient content in the diet. This analysis merged dietary data from four intervention studies in participants with varying health conditions and examined the effect of increased FV consumption on diet profile. Dietary intake was assessed by either diet diaries or diet histories used in four FV randomised intervention studies. All food and drink intake recorded was analysed using WISP version 3.0, and FV portions were manually counted using household measures. Regression analysis revealed significant increases in intakes of energy (172 kJ (+41 kcal)), carbohydrate (+3·9 g/4184 kJ (1000 kcal)), total sugars (+6·0 g/4184 kJ (1000 kcal)) and fibre (+0·8 g/4184 kJ (1000 kcal)) and significant decreases in intakes of total fat (−1·4 g/4184 kJ (1000 kcal)), SFA (−0·6 g/4184 kJ (1000 kcal)), MUFA (−0·6 g/4184 kJ (1000 kcal)), PUFA (−0·1 g/4184 kJ (1000 kcal)) and starch (−2·1 g/4184 kJ (1000 kcal)) per one portion increase in FV. Significant percentage increases were also observed in vitamin C (+24 %) and -carotene (+20 %) intake, per one portion increase in FV. In conclusion, pooled analysis of four FV intervention studies, that used similar approaches to achieving dietary change, in participants with varying health conditions, demonstrated an increase in energy, total carbohydrate, sugars and fibre intake, and a decrease in fat intake alongside an expected increase in micronutrient intake.